2003
DOI: 10.1289/ehp.5620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chinese domestic polychlorinated biphenyls (PCBs) on gonadal differentiation in Xenopus laevis.

Abstract: To determine whether polychlorinated biphenyls (PCBs) influence gonadal differentiation in Xenopus laevis, tadpoles were exposed to two Chinese domestic PCBs (PCB 3 and PCB 5) from Nieuwkoop and Faber stage 46/47 to complete metamorphosis. Gonads were characterized using a dissecting microscope. The control X. laevis had normal ovaries or testes in gross morphology, whereas obviously abnormal testes including ovotestes were found in PCB 3- and PCB 5-exposed groups. Ovotestes were characterized by morphologic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 43 publications
(39 reference statements)
0
30
0
Order By: Relevance
“…In 1999, Kloas et al reported that bisphenol A and 4-nonylphenol caused a significantly higher number of female phenotypes compared to control X. laevis, which is the first evidence that endocrine disruptor can induce feminization in X. laevis (1999). Since then, there has been increasing data on feminizing effects of endocrine disruptors on X. laevis, such as atrazine, polychlorinated biphenyls and bisphenol A (Hayes et al, 2002;Qin et al, 2003;Levy et al, 2004) despite contrary results reported as well Carr et al, 2003). In this study, we for the first time report that the phytoestrogen quercetin also has influence on the gonadal developemt in X. laevis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In 1999, Kloas et al reported that bisphenol A and 4-nonylphenol caused a significantly higher number of female phenotypes compared to control X. laevis, which is the first evidence that endocrine disruptor can induce feminization in X. laevis (1999). Since then, there has been increasing data on feminizing effects of endocrine disruptors on X. laevis, such as atrazine, polychlorinated biphenyls and bisphenol A (Hayes et al, 2002;Qin et al, 2003;Levy et al, 2004) despite contrary results reported as well Carr et al, 2003). In this study, we for the first time report that the phytoestrogen quercetin also has influence on the gonadal developemt in X. laevis.…”
Section: Discussionmentioning
confidence: 64%
“…Miyata et al treated X. laevis with 100 g/L estradiol (E 2 ) and obtained 100% females (1999). There is increasing evidence that endocrine disruptors with estrogenic activities also can induce gonadal feminization in X. laevis and affect sexual hormone homeostasis (Kloas et al, 1999;Hayes et al, 2002;Qin et al, 2003;Levy et al, 2004). In our previous study, X. laevis was suggested to be good model animal for assaying endocrine disruptors (Qin et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…PCBs. Annual PCB production in China was estimated to be ten thousand tonnes between 1965 and 1974 (20). Because PCBs have been banned, current atmospheric PCB pollution is likely due to emissions from disposal or accidental release of products containing PCBs and volatilization from environmental reservoirs.…”
Section: Resultsmentioning
confidence: 99%
“…The domestic products of technical PCBs were named PCB 3 and PCB 5 , which compositions were almost similar to those of Arochlor 1242 and 1254, respectively (Jang et al, 1997). China's total production was 10,000 t of which 9000 t was PCB 3 and 1000 t was PCB 5 (Qin et al, 2003). Most of PCB 3 products have been used as dielectric fluids in electric capacitors, and most of PCB 5 products as additives in paints (Jang et al, 1997).…”
Section: Introductionmentioning
confidence: 99%